Thea Stilton and the dragon's code - Bono, Fabio (New York : Scholastic, 2009)
Thea Stilton and her journalism class try to find a missing student.
"English translation... by Atlantyca S.p.A."--T.p. verso.
RL3.
007-010.
Keywords: Mice -- Fiction; Missing persons -- Fiction; Journalists -- Fiction; Schools -- Fiction; Teachers -- Fiction; Mystery and detective stories